AGRIBISNIS HORTIKULTURA: PELUANG DAN TANTANGAN DALAM ERA PERDAGANGAN BEBAS - BAMBANG IRAWAN (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2003)
During two last decades food trade in the world market was shift to horticulturalproducts such as fruits and vegetables. Household consumption of the products also tends toincrease in domestic market due to the increase of income per caput, induced by economicgrowth. The two tendencies reveals that market of horticultural products will increase in thefuture both in domestic and world markets, and barier of entry to the market will beeliminated in the era of trade liberalisation. It is true that Indonesia had a surplus in the tradeof horticultural products, comes particularly from fruits trade, but this surplus is continuouslydecreasing resulted from decrease of competitiveness of local agribusiness compared withthose from Africa and Southern America countries particularly. To increase competitivenessof local agribusiness, future development of horticulture sector should be focused on threeefforts : (1) Development of vertically integrated agribusiness so that horticulturalagribusiness has capability to respond market demand effectively. This effort can beimplemented through development of partnership business system between input trader,farmer and output trader. (2) Price stabilization of horticultural products, which can be takenby establishment of regional agribusiness institution across producer regions. The main taskof the institution is to regulate supply quantity of overall producer adjusted to marketrequirement. (3) Facilitation of post harvest infrastructure to farmers in order to retarddegradation of product quality and to improve bargaining position of farmers in the priceformation at producer market.